Review of the family Platyxanthidae Guinot, 1977 (Crustacea, Decapoda, Brachyura, Eriphioidea), with the description of a new genus and a key to genera and species - Thoma, Brent P.; Ng, Peter K. L.; Felder, Darryl L. (Zootaxa, 2012)
During recent studies of phylogenetic relationships within Eriphioidea (sensu Ng et al. 2008), we recovered molecularevidence that the genus Platyxanthus A. Milne-Edwards, 1863, was not monophyletic. This prompted detailedmorphological examination of the group, which confirmed that clear differences in characteristics of the carapace, firstmale pleopod, antennae, antennules, epistome, abdomen, and thoracic sternum serve to separate the species ofPlatyxanthus into three distinct groups. Comparison of the type material of Peloeus cokeri (Rathbun, 1930), (formerlyPlatyxanthus cokeri) to Peloeus armatus Eydoux & Souleyet, 1842, indicated that P. cokeri is a junior synonym of P.armatus and that Gordonoxanthus Števčić, 2011 (type species Platyxanthus cokeri Rathbun, 1930) is thus a juniorsynonym of Peloeus. Danielethus n. gen. is described to accommodate Platyxanthus patagonicus A. Milne-Edwards,1863, and Platyxanthus crenulatus A. Milne-Edwards, 1863. A key to the known genera and species of the family Platyxanthidae Guinot, 1977 is provided.